Delayed vacuolation in mammalian cells caused by hypotonicity and ion loss - Emily Zook; Yingzhou Edward Pan; Anna Wipplinger; Hubert H. Kerschbaum; Robert J. Clements; Markus Ritter; Tobias Stauber; Michael A. Model (Scientific Reports)
Abstract Prolonged exposure of mammalian cells to hypotonic environments stimulates the development of sometimes large and numerous vacuoles of unknown origin. Here, we investigate the nature and formation of these vacuoles, which we term LateVacs. Vacuolation starts after osmotic cell swelling has subsided and continues for many hours thereafter. Most of the vacuoles are positive for the lysosomal marker LAMP-1 but not for the autophagosomal marker LC3. Vacuoles do not appear to have acidic pH, as they exclude LysoTracker and acridine orange; inhibiting the V-ATPase with bafilomycin A1 has no effect on their formation. No LateVacs were formed in cells with a knockout of the essential LRRC8A subunit of the volume-regulated anion channel (VRAC). Since the main feature of cells recovered from hypotonic swelling should be reduced chloride concentration, we tested if chloride depletion can act as a signal for vacuolation. Indeed, four different low-chloride buffers resulted in the development of similar vacuoles. Moreover, vacuolation was suppressed in WNK1/WNK3 double knockouts or by the inhibition of WNK kinase, which is activated by low chloride; in hypotonic media, the WNK inhibitor had a similar effect. However, exposing cells to a low-sodium, high-potassium medium also resulted in vacuoles, which were insensitive to WNK. We conclude that vacuole development can be triggered either by the loss of chloride or by the loss of sodium.